Retinal Surgery Evolution with New Trends - Pradeep Kumar; Sanjay Kumar Mishra; Amrita Joshi; Deepesh Unni; Alok Sati; Supriya Dhar (Delhi Journal of Ophthalmology)
Retinal surgery has undergone a complete transformation in the past century. The earliest reported results of Gonin et al. with ignipuncture in 1923 heralded the scientifically evidenced treatment of retinal detachment. The article follows the subsequent landmark developments in the field of retinal detachment surgery in the form of external buckles, cryotherapy, laser photocoagulation, operating microscopes with inverter, wide-angle viewing systems, vitrectomy, vitreous substitutes, and endolaser that have been deliberated on. The recent developments in the past two decades which have reshaped retinal surgery from a last-stage procedure to an early option for visual rehabilitation in the form of smaller gauges for vitrectomy, chandelier illumination, valved cannulas, intraoperative intraocular pressure control, role of anti-vascular endothelial growth factors, and heads-up viewing systems have also been elaborated.